Petri-net and GA-based approach to modeling, scheduling, and performance evaluation for wafer fabrication. - Jyh-Horn Chen (IEEE Transactions on robotics and automation)
A genetic algorithm (GA) embedded search strategy over a colored timed Petri net (CTPN) for wafer fabrication is proposed. Through the CTPN model, all possible behaviors of the wafer manufacturing systems, such as WIP status and machine status, can be completely tracked down by the reachability graph of the net. The chromosome representation of the search nodes in GA is constructed directly from the CTPN model, recording information about the appropriate scheduling policy for each workstation in the fabrication. A better chromosome found by GA is received by the CTPN based schedule builder, and a near-optimal schedule is then generated